Efektivitas Program Akademi Berdaya dan Keberdayaan Penjahit Perempuan di Kecamatan Cikampek, Kabupaten Karawang - Sabrina, Hana Anugrah; Indriana, Hana (Institut Teknologi Sepuluh Nopember, 2025)
An empowerment program can be said to be effective and successful if the beneficiary community is empowered. The women's empowerment approach focuses on women's capacity framework in increasing independence and internal strength. However, empowerment programs are still found that do not target communities with the right needs. BaitulMaalKu as an Amil Zakat institution contributes to empowering women in the fields of sewing and fashion design to increase independence. The aim of this research is to analyze the relationship between the level of program effectiveness and the empowerment of women who are beneficiaries of the Empowered Academy program. The number of research respondents was 43 women recipients of the Empowered Academy program who were selected using census techniques. The results of the research show that there is no significant relationship between the level of effectiveness of the empowerment program and the level of empowerment of women who receive the benefits of the Empowered Academy. In general, the level of women's empowerment is not only determined by the level of program effectiveness. Women's empowerment is determined by opportunities for access to credit, doing productive work, and the ability to start a business